A Study of Teacher’s Meaningful Learning Activities in The Teaching Process of Intermediate Grammar Learning Course (RETAIN, 2018)
Abstrak Menurut Hsu (2013) grammar adalah struktur bahasa, dalam konteks ini, dari bahasa Inggris. Maka penting bagi guru untuk memberikan pengajaran grammar yang efektif kepada siswa. Salah satu cara adalah melalui Meaningful Learning, prinsip mengajar bahasa yang diusulkan oleh Brown. Untuk mencapai Meaningful Learning, aspek retention (retensi) and transfer of knowledge (transfer ilmu pengetahuan) harus dipromosikan dan dilibatkan dengan siswa. Oleh karena itu, penelitian ini bertujuan untuk mendeskripsikan dan menganalisis kegiatan Meaningful Learning retention (retensi) dan transfer of knowledge (transfer ilmu pengetahuan) dalam proses pengajaran yang dilakukan oleh seorang guru yang mengajar kelas intermediate grammar. Teori yang digunakan dalam penelitian ini adalah teori Meaningful Learning dari Brown dan teori proses kognitif dari Meyer (2002). Teori milik Mayer menyajikan 18 proses kognitif yang digunakan untuk menganalisis kegiatan Meaningful Learning di kelas. Penelitian ini merupakan penelitian deskriptif yang menggunakan teknik metode kualitatif. Sumber data untuk penelitian ini adalah tindakan guru, baik lisan (dalam bentuk ucapan guru, kalimat) dan non-verbal (dalam bentuk kegiatan mengajar). Berdasarkan analisis data yang diperoleh, ditemukan bahwa guru telah mempromosikan aspek retention (retensi) dan transfer of knowledge (transfer ilmu pengetahuan) Meaningful Learning dalam kegiatan mengajar grammar. Proses kognitif yang dilakukan dengan siswa untuk retensi adalah kegiatan mengingat, menjelaskan, mencontohkan, mengklasifikasikan, membandingkan, dan meringkas, sementara pada transfer ilmu pengetahuan adalah kegiatan membedakan, mengatur, menghubungkan, melaksanakan, dan menciptakan.Kata Kunci : Grammar, Prinsip mengajar, Meaningful learning, Proses kognitifAbstractAccording to Hsu (2013) grammar is the structure of the language, which in this case, English language. Thus, it is important for teachers to provide an effective grammar teaching to the students. One way to achieve this is through Meaningful Learning, a language teaching principle by Brown. In order to achieve Meaningful Learning, retention and transfer of knowledge aspect should be promoted are to be engaged with the students. Therefore, this study aims to describe and analyze the meaningful learning activities of retention and transfer of knowledge done by a teacher of an intermediate grammar class in their teaching process. The main theories used in this study are Brown’s Meaningful Learning and Meyer’s (2002) cognitive processes of meaningful learning. The latter theory provides 18 cognitive processes which was used to analyze the meaningful learning activities in the classroom. This study is a descriptive research that used qualitative method technique. The source of data for this study is the teacher’s actions, both verbal (in form of teacher’s utterance, sentences) and non-verbal (in form of teaching activities). Based on the analysis of the obtained data, it was found that the teacher has promoted both meaningful learning retention and transfer of knowledge aspects in her grammar teaching activities. The cognitive processes engaged with the students for retention were recalling, explaining, exemplifying, classifying, comparing, and summarizing activities, meanwhile for transfer of knowledge were differentiating, organizing, attributing, execute, and generating activities.Keywords: Grammar, Teaching principles, Meaningful learning, Cognitive process